2006
DOI: 10.1186/1471-2105-7-483
|View full text |Cite
|
Sign up to set email alerts
|

Novel metaheuristic for parameter estimation in nonlinear dynamic biological systems

Abstract: Background: We consider the problem of parameter estimation (model calibration) in nonlinear dynamic models of biological systems. Due to the frequent ill-conditioning and multi-modality of many of these problems, traditional local methods usually fail (unless initialized with very good guesses of the parameter vector). In order to surmount these difficulties, global optimization (GO) methods have been suggested as robust alternatives. Currently, deterministic GO methods can not solve problems of realistic siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(154 citation statements)
references
References 57 publications
(50 reference statements)
4
150
0
Order By: Relevance
“…Rodriguez-Fernandez et al [5] studied the same kinetic model for the isomerization of α-pinene and applied a global optimization based on the Scatter Table 2 Table 2, it shows roughly 86%, 76%, 33%, 38%, and 28% higher values. This point is also mentioned by Rodriguez-Fernandez et al [5] that the confidence intervals obtained from the Fisher information matrix show a wider confidence interval.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Rodriguez-Fernandez et al [5] studied the same kinetic model for the isomerization of α-pinene and applied a global optimization based on the Scatter Table 2 Table 2, it shows roughly 86%, 76%, 33%, 38%, and 28% higher values. This point is also mentioned by Rodriguez-Fernandez et al [5] that the confidence intervals obtained from the Fisher information matrix show a wider confidence interval.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction produces four products that are presented in weight fraction in eight intervals each with duplicated results. Hunter et al [17] proposed a kinetic model for this reaction as it is shown in Figure 1 followed by Equations (1) to (5). In this scheme α-pinene (C 1 ) converts to dipentene (C 2 ) and allo-ocimen (C 3 ) in two parallel paths; dipentene is the end-point component but allo-ocimen yields α-and β-pyronene (C 4 ) and involves in an equilibrium reaction with other dimer compounds (C 5 ).…”
Section: Kinetic Modelmentioning
confidence: 99%
See 3 more Smart Citations